Approaches to priority identification in digital health in ten countries of the Global Digital Health Partnership - Cascini, Fidelia; Altamura, Gerardo; Failla, Giovanna; Gentili, Andrea; Puleo, Valeria; Melnyk, Andriy; Causio, Francesco Andrea; Ricciardi, Walter (Frontiers in Digital Health, 2022)
To promote shared digital health best practices in a global context, as agreed within the Global Digital Health Partnership (GDHP), one of the most important topics to evaluate is the ability to detect what participating countries believe to be priorities suitable to improve their healthcare systems. No previously published scientific papers investigated these aspects as a cross-country comparison. The aim of this paper is to present results concerning digital health priorities identification as a section of the Evidence and Evaluation survey addressed to GDHP members in 2020, comparing countries’ initiatives and perspectives for the future of digital health based on internationally agreed developments. This survey followed a cross-sectional study approach. An online survey was addressed to the stakeholders of 29 major countries. Ten out of 29 countries answered the survey. The mean global score of 3.54 out of 5, calculated on the whole data set, demonstrates how the global attention to a digital evolution in health is shared by most of the evaluated countries. The resulting insights on the differences between digital health priority identification among different GDHP countries serves as a starting point to coordinate further progress on digital health worldwide and foster evidence-based collaboration.